Factors pertaining to students motivation towards academic achievement: a case study in the emirate of Abu Dhabi - Dev, Smitha; Qureshi, Rubina; Nair, Sreethi; Khowaja, Erum (International Journal of Psychosocial Rehabilitation, 2020)
In the context of the UAE and other GCC countries, student motivation is a big struggle for university educators. Based on our experiences as educators in many humanities and social science classrooms, we have observed that students often rely on extrinsic motivation for their learning and mainly depend on their teachers to take the responsibility of their learning. This paper is designed to study a number of factors affecting students’ motivation in humanities, especially in Psychology and Society courses in a General Education Program setting. The study was conducted on 370 students from Abu Dhabi. Motivation scales were used to understand the various factors contributing to their motivation in learning. The data was analyzed using various statistical techniques such as t-test, f-test and Chi-square test. The results provide profound insights into numerous factors affecting students in their learning process.